KEBIJAKAN PEMERINTAH INDONESIA DALAM MEMPERTAHANKAN IRIGASI (SUBAK) DI LINGKUNGAN MASYARAKAT BALI PASCA DIRESMIKAN SEBAGAI WARISAN BUDAYA - M. Hidayat Budiarto; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Subak is a community organization which specifically regulate irrigation system used in rice cultivation in Bali, Indonesia. Subak usually has a temple called Pura Uluncarik or Pura Bedugul, specially built by farmers and is destined for the goddess of prosperity and fertility goddess Sri. This irrigation system is governed by an indigenous leader who also is a farmer in Bali. The purpose of the program is as an arrangement Subak irrigation when there is water shortage, as well as for communication and structural coordination. As each Subak it has a membership as well as the division of the Regional Budget / Bylaws respectively. This study aims to know the progress and constraints to maintain water control system in Indonesia.This study uses a qualitative research approach (International Politic). Data was collected by means of a research library (Library research), data is said to be from books, journals, magazines, newspapers and other sources (document analysis). I also use the internet facilities in the process of collecting data related to and relevant to the issues discussed in this study. The data analysis technique based on the cycles Huberman and Miles in the form of data collection, data reduction, organizing data, and conclusions.Jatiluwih as a World Cultural Heritage (World Cultural Heritage) due to the potential form of Subak actualized by paddy terracing very unique and very different from other Subak and supported by the agrarian society of religious life in support of or as the spearhead of the community Subak Jatiluwih. This is the plus points of UNESCO to establish Jatiluwih as a World Cultural Heritage. In the process, people Jatiluwih have not yet benefited from the establishment of Jatiluwih as a World Cultural Heritage, so that the public be less responsive to the rights and obligations as a consequence designated as the World Cultural Heritage. To that end, it is necessary to look for a way out for the World Cultural Heritage status -Right correctly perceived by the public Jatiluwih positive benefits, especially the Subak. Consequences Jatiluwih as a World Cultural Heritage is that Jatiluwih started much visited by tourists, both foreign and domestic tourists to see firsthand the beauty of the fields terracing and the subak system. With the creativity of Jatiluwih Subak communities will be able to contribute to tourism in general in favor of Jatiluwih as a World Cultural Heritage. Thus, local communities feel they have benefited from the development of tourism in Jatiluwih and their status in the World Cultural Heritage. In addition, the sustainability of rice paddies along Subak terracing imbued with Hinduism also defensible.Keyword : SUBAK, World Cultural Heritage, Irrigation Bali